Multivariate statistical classification of beach sands along the coastal belt of Ghana using natural radioactivity data - Lawluvi, H (University of Ghana, 2016)
The study investigated multivariate statistical data reduction strategy for environmental monitoring using radioactivity data. The activity concentrations of 232Th, 238U series and 40K in beach sands along the coastline of Ghana have been measured using gamma spectroscopy. The mean specific activity of 238U measured ranged ranges from 1.87 to 27.00 Bq Kg-1, 232Th content ranges from 2.50 to 26.90 Bq Kg-1 and 40K content ranges from 47.80 to 276 Bq Kg-1. The values obtained in this study are comparable with published data from other works done in Ghana indicating that the study area has not been affected until now by any NORM activities that may have started in these environments. The study shows that the average Raeq value 30.93 Bq Kg-1 for the studied area is lower than the internationally accepted value 370 Bq Kg-1. The corresponding values for the external hazard and internal hazard indices are 0.08 and 0.11 respectively. The Hex and Hm values which are lower than the internationally accepted value of one (1.00) may not pose any significant radiological hazard to users of these sands and beaches. Hierarchical cluster analysis was used to partition the activity concentrations into non-overlapping clusters; the dendrograms revealed that 238U and 232Th contribute more to the Hazard Indexes than 40K and the number of sampling towns can be reduced from the present 41 to 8 towns. From the analysis, it is possible to design an optimal sampling strategy, which could reduce; the number of parameters to be measured, the number of sampling stations, the number of samples collected and associated costs.
Thesis (PhD) - University of Ghana, 2016
Keywords: ENVIRONMENTAL SCIENCES; ISOTOPES; RADIATION SOURCES; ABSORBED RADIATION DOSES; HAZARDS; Ghana